Exclusion of Pregnant Women from Clinical Trials during the Coronavirus Disease 2019 Pandemic: A Review of International Registries - Smith, Devin D.; Pippen, Jessica L.; Adesomo, Adebayo A.; Rood, Kara M.; Landon, Mark B.; Costantine, Maged M. (American Journal of Perinatology, 2020)
Objective Pregnant women have been historically excluded from clinical trials for nonobstetric conditions, even during prior epidemics. The objective of this review is to describe the current state of research for pregnant women during the coronavirus disease 2019 (COVID-19) pandemic.Study Design We conducted a search of international trial registries for trials relating to the novel coronavirus. The eligibility criteria for each trial were reviewed for inclusion/exclusion of pregnant women. Relevant data were extracted and descriptive statistics were calculated for individual and combined data. The total number of trials from each registry were compared, as well as the proportions of pregnancy-related trials within each.Results Among 621,370 trials in the World Health Organization International Clinical Trials Registry, 927 (0.15%) were COVID-19 related. Of those, the majority (52%) explicitly excluded pregnancy or failed to address pregnancy at all (46%) and only 16 (1.7%) were pregnancy specific. When categorized by region, 688 (74.2%) of COVID-19 trials were in Asia, followed by 128 (13.8%) in Europe, and 66 (7.2%) in North America. Of the COVID-19 trials which included pregnant women, only three were randomized-controlled drug trials.Conclusion Approximately 1.7% of current COVID-19 research is pregnancy related and the majority of trials either explicitly exclude or fail to address pregnancy. Only three interventional trials worldwide involved pregnant women. The knowledge gap concerning the safety and efficacy of interventions for COVID-19 created by the exclusion of pregnant women may ultimately harm them. While “ethical” concerns about fetal exposure are often cited, it is in fact unethical to habitually exclude pregnant women from research.Key Points
Keywords: coronavirus; COVID-19; exclusion; pregnancy; research